Assessment of Trace Metal Disturbances in Healthcare Workers Exposed to Low Dose Ionizing Radiations in a Tertiary Care Hospital - Ghauri, Ahsan Ahmad; Muhammad Usman Munir; Zujaja Hina Haroon; Muhammad Aamir; Muhammad Babar Khan; Sobia Irum Kirmani (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the effects of ionizing radiations on trace metal levels in healthcare workers exposed to occupational radiation in a tertiary care health facility.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Chemical Pathology & Endocrinology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, in collaboration with the Department of Radiology, Combined Military Hospital, Rawalpindi Pakistan, from Apr to Oct 2021.Methodology: Healthcare workers (n=45) exposed to occupational radiations were compared with an equal number of Controls in a tertiary care health facility for their trace metal levels. An atomic absorption spectrophotometer (AAS) was used to measure serum zinc (Zn) and copper (Cu) levels. A calorimetric technique was used to measure serum iron (Fe) levels.Results: Mean serum Copper (9.54±2.52 µmol/l) and Zinc (11.78±1.90 µmol/l) concentrations of the Risk-Group were significantly lower than their respective Control-Groups (Copper: 14.76±3.13 µmol/l and Zinc: 14.67±3.01 µmol/l). At the same time, mean serum Iron levels in the Exposed-Group (17.55±3.88 µmol/l) were significantly (p